ROAD TRAFFIC SAFETY STRATEGY IN UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article proposes some new benchmarks and certain unconventional solutions for defining a contemporary road safety strategy in Ukraine at both conceptual and legal levels, taking into account progressive European experience. Several critical judgments are expressed regarding Ukraine’s existing state policy in the field of road safety and transport operation, as well as the strategic normative acts. A series of arguments are provided in favor of the greater effectiveness of the concept of social realism compared to the concept of legal idealism, upon which the existing state policy in this area is based. The key responsibilities of patrol police units and the main methods of their activities, which are supposed to form the basis for ensuring road safety by this entity in practice, are outlined. A range of relevant directions that should be considered in the new National Road Safety Strategy in Ukraine for the period up to 2030 are highlighted
Keywords: road safety; strategy; Vision Zero; repression; prevention; crime; violations; road traffic fatalities and injuries